ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Martiana Sani, 10.05.52.0006; Sri Mindarti, Ceacilia (Students Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of the KAP size, financial distress, stock ownership, management changes, and audit opinion on auditor changes. The issue of independence is the main cause of the auditor changes is mandatory in Indonesia. Auditor changes can occur because of regulations requiring compulsory and can happen voluntarily. The data used in this study is data companies listed in Indonesia Stock Exchange in 2010-2012. The research used proporsive sampling and obtain a sample of 45 data the reseach. The data reseach then tested by logistik regression using SPSS 19 application to test the effect of the KAP size, financial distress, stock ownership, and managemen changes, and audit opinion on auditor changes. The results of this study indicate that the audit opinion significantly has effect on auditor changes, while the KAP size, financial distress, stock ownership, and management changes do not have effect on auditor changes.Keywords: Auditor changes, KAP size, financial distress, stock ownership, management changes and audit opinionÂ